Spinirta gen. nov., a new dark sac spider genus from southern China (Araneae: Corinnidae) - Jin, Chi; Zhang, Feng (Zootaxa, 2020)
A new genus of the spider family Corinnidae, Spinirta gen. nov., with nine new species is described from southern China: S. jinyunshanensis sp. nov., S. forcipata sp. nov., S. sparsula sp. nov., S. aurita sp. nov., S. aviforma sp. nov., S. quadrata sp. nov., S. leigongshanensis sp. nov., S. qizimeiensis sp. nov. and S. rugosa sp. nov.. Further, one species is transferred from Allomedmassa Dankittipakul & Singtripop, 2014 to this new genus as Spinirta qiaoliaoensis (Lu & Chen, 2019) comb. nov.. The new genus is a close relative of Allomedmassa, Medmassa Simon, 1887 and Paramedmassa Jin, Zhang & Zhang, 2019, but can be distinguished by the unique spines on the ventral surface of the RTA of the male palp, and the anteriorly situated, large, separated COs or fused into a large atrium of the female epigyne.